Relevansi Filsafat Eksistensialisme dalam Kehidupan Modern - Erwin Eka Saputra (Journal of Humanities, Social Sciences, and Education, 2025)
Existentialism philosophy is a school of philosophy that emphasizes individual freedom, responsibility, choice, and the meaning of life determined by humans themselves. In the era of modern life marked by identity crises, social pressures, and the complexity of life choices, existentialist values ​​are becoming increasingly relevant. This literature study aims to analyze the relevance of existentialism in modern life by reviewing the thoughts of key figures such as Søren Kierkegaard, Friedrich Nietzsche, Jean-Paul Sartre, and Albert Camus. This study uses a qualitative approach with a literature study method of philosophical works, scientific articles, and contemporary reflections. The results of the study show that existentialism philosophy provides a critical foundation for the existential problems of today's humans, such as social alienation, loss of meaning, and the search for self-authenticity. Existentialism also emphasizes the importance of authenticity and personal responsibility amidst modern tendencies towards conformity and hedonism. Thus, this philosophy is not only theoretical, but also applicable in shaping individual existential awareness. This study concludes that existentialism offers a relevant philosophical perspective to address the various psychological and spiritual challenges of modern humans.